The effects of 12 weeks body balance and pelvic floor muscles exercise on back pain intensity during pregnancy - Mohammad Reza Ramezanpour; Mansooreh Mohammad nezhad; Farideh Akhlaghi (Mashhad University of Medical Sciences, 2018)
Introduction: Back pain is one of the most common musculoskeletal disorders that most women experience it for the first time during pregnancy. Back pain during pregnancy can cause disability or reduced quality of life. Sport exercise is one of the choices in treatment and prevention of back pain during pregnancy and seems that doesn't have the limitations and complications of other treatment methods. This study was performed with aim to compare the effects of 12 weeks body balance and pelvic floor muscles exercise on back pain intensity during pregnancy. Methods: This semi-experimental study was performed on 60 primigravida women with pregnancy pack pain in 2015. The Participants were placed in four groups of 15 cases: body balance, Kegel exercise, combination of body balance and Kegel exercises, and control; they performed these exercises for 12 weeks. Data collection tool was VAS 10 marks, and the patient's pain score was recorded before doing the exercises and also at last month of the pregnancy. Data was analyzed by SPSS software (version 16) and Kolmogrov-Smirnov, paired-t and ANOVA tests. P≤0.05 was considered significant. Results: At the end of the intervention, mean of pregnancy back pain significantly reduced in the groups of body balance and combination of exercise (p<0.05), although the mean of pregnancy back pain in Kegel group reduced after exercise, but was not significant (P=0.138). The mean of pregnancy back pain significantly increased in control group (P=0.0001). There was significant difference between Kegel exercise and combination of body balance and Kegel exercises on pregnancy back pain (P=0.0006). Also, 12 weeks body balance, Kegel exercise and combination of body balance and Kegel exercises had significant effects on reduction of pregnancy back pain intensity (P=0.0001). Conclusion: Exercise protocol based on the body balance and Kegel improves pregnancy back pain, but body balance exercise causes more reduction in pregnancy back pain.